Comparative study of polymorph nanosheet materials for emerging metal-ion batteries - Soares, Davi Marcelo (Kansas State University, 2021)
Rechargeable batteries have attained strategic place in applications involving transportation, microelectronics, and electric power grid in the past 30 years. Yet in a society that strives to achieve both sustainability and economic growth the concern whether lithium and cobalt reserves may supply the future demand of multibillion-dollar industries and emerging markets has risen. To address this concern, research on novel rechargeable batteries composed by earth-abundant elements has re-gained traction recently. As potential candidates for beyond lithium-ion battery (LIB) technologies, both sodium and potassium present low cost, reserves more globally distributed, and redox potentials closer to that of lithium metal. Likewise, from the knowledge consolidated over decades on LIBs, certain lessons learnt can be applied in the study of these emerging alkali metal ion batteries. One of these lessons is that to enable the use of sodium- and potassium-ion battery technologies a comprehensive study of crystal structure and electrochemical processes happening in electrode materials is crucial. In this scenario, a class of materials known as transition metal dichalcogenides (TMDs), whose structure was first determined by Linus Pauling in 1923, has re-gained attention due to layered and wide variety of species and chemistries. To date, approximately 60 species of TMDs are known, in which two thirds present layered structure and polymorphism. Conducted in the 1970s by the 2019 Nobel Prize in Chemistry, M. Stanley Whittingham, research on layered TMDs for electrochemical energy storage applications was shortly abandoned owing to poor stability of TMDs. Upon the increasing interest on layered materials in the 2000s, TMD nanosheets were found to have relatively higher uptake and faster diffusion of Li⁺, Na⁺, and K⁺ in their host structure -- leading to high theoretical capacity and rate capability, respectively. Nevertheless, along with the fascinating properties of TMDs -- some yet to be unveiled – research challenges are also still present. Molybdenum disulfide (MoS₂) is a layered TMD that presents polymorphism, high specific capacity towards sodium-ions and abundant availability on earth. However, MoS₂ as sodium-ion battery (SIB) electrode shows poor cycle stability and fast capacity degradation, due to low electronic conductivity, and low reversibility. To address the stability issue of MoS₂, this thesis explored synthesis of a novel composite material of 2H-MoS₂ functionalized with a thin layer of molecular precursor-derived silicon oxycarbide (SiOC) ceramic as electrode for sodium-ion battery (SIB). The functionalized MoS₂ electrode was able to overcome shortcomings of pristine 2H-MoS₂ electrodes in SIB. The improved stability was attributed to the SiOC, a ceramic material that safeguarded the active material (MoS₂) without compromising sodiation and de-sodiation processes. Moreover, SiOC provided free carbon domains that showed increased electronic conductivity of functionalized MoS₂, as evidenced by the rate capability test. Electrochemical results show that specific capacity of MoS₂-SiOC was 12 times higher than pristine MoS₂ at 200 mA g⁻¹. Later, in view of the larger interlayer spacing and unique electronic properties of some layered telluride-based TMDs, tungsten ditelluride (WTe₂) was selected as host material for studies involving potassium-ion storage. In addition to providing a detailed description of crystal phase of the thermodynamically stable Td phase of WTe₂ at room temperature, this thesis introduces a discussion regarding electrochemical impedance spectroscopy (EIS), a frequency domain analysis that can provide useful information for electrochemical systems. Findings shows that due to higher interlayer spacing and conversion type-reactions – confirmed by ex-situ post-cycling analysis -- Td-WTe₂ showed first cycle specific charge capacity of 3.3 K⁺ stored per WTe₂ molecule, stable capacity of 143 mA h g⁻¹ at 10th cycle number -- outperforming WS₂ and graphite -- reasonable cycling stability, and low charge transfer resistance. This is the first known work in the field to highlight the potential of Td-WTe₂ as potassium-ion battery (KIB) electrode. Td-WTe₂ was also employed as electrode material in a study of diffusivity of Na⁺ and K⁺ in SIB and KIB half-cells, respectively. Although in the literature there are reports that suggest the larger ionic radius of K⁺ (1.33 Å) -- in comparison to Na⁺ (0.97 Å) – lead to an inferior electrochemical performance of KIBs, in this work we demonstrated that KIB outperforms the SIB cell in terms of rate capability and cycling stability. This behavior was explained by Stokes' radius concept of Na⁺ and K⁺ in propylene carbonate (PC) based electrolyte, which explains the higher mobility of K⁺ in the electrolyte medium. These findings corroborate the potential of semimetal TMD electrode materials and highlight how electrolyte medium has implications on electrochemical performance of electrode materials. In summary, the scientific contributions attained in this research work intend to support the current development and understanding of novel sulfide- and telluride-layered TMDs materials for sodium- and potassium-ion batteries, respectively.
Keywords: Batteries; Transition metal dichalcogenides; Lithium-ion; Sodium-ion batteries; Potassium-ion batteries; Layered materials